AN EFFECTIVE CONTROL OF AN ISOLATED INDUCTION GENERATOR SUPPLYING DC LOAD FOR WIND POWER CONVERTING APPLICATIONS - L. Louze (National Technical University "Kharkiv Polytechnic Institute", 2020)
Purpose. The aim of this paper is to perform a simple and robust control method based on the well-known sliding control approach for a self-excited induction generator supplying an isolated DC load; this adopted technique does not require much computation and could be easily implemented in practice. In this context, the present work will begin with a mathematical development of this control technique and its application to the self-excited induction generator case. For this purpose, the machine provides the produced active power to the load through a static PWM converter equipped with a single capacitor on the DC side. In order to insure the output DC-bus voltage regulation with respect to the load-power demands and the rotor speed fluctuations, the required stator currents references are computed by considering the reactive power required for the machine core magnetization, the induced voltages through the stator windings and the active power set value obtained from the corresponding sliding mode DC-bus voltage controller. Regarding the nonlinearity of the DC-bus voltage mathematical model and the discontinuity characterizing the converter-machine behavior association, the sliding mode strategy will constitute a perfect tool to sizing the controller structure with high control performances. Results of simulation carried out to demonstrate the proposed control validity are presented.